Tinjauan Yuridis Perlindungan Hukum Terhadap Pengguna Automated Teller Machine (Atm) Di Pt. Bank Pembangunan Daerah Jawa Timur, Tbk - Tamsarasty, Devynta Kusretno; , Inayah, S.H., M.H (2016)
One of the services rendered to the community bank is the Automated Teller Machine (ATM). ATM is one form of banking products result of technology (computers) in order to increase banking services to customers. ATM is able to replace the function of money as means of payment, the use of ATM is felt more safe and practical for all purposes. The method used is empirical juridical approach and the type of research is descriptive research. The data source of primary data sourced from interviews and additional form of legislation and regulations, and secondary data obtained from the literature. Data were collected by study of documents and interviews. And methods of data analysis used is qualitative analysis. The conclusion of this study are: (1) In the conduct of legal protection given to the Customer's Bank Jatim Peraturn accordance with the Bank Indonesia. Evidenced in the form Conditions and Special Terms Savings Bank Jatim "If a bank ATM card is lost, Savers shall report orally to the info Bank / Branch nearest to the blocking process. (2) legal efforts can be made by Customer who suffered losses may submit complaints with respect to the use of an ATM card.